Changing the face of earth engineering geomorphology : proceedings of the 28th Binghamton Symposium in Geomorphology, held 28 August to 3 September 1997 in Bologna - Binghamton Symposium in Geomorphology (28th : 1997 : Bologna, Italy); Giardino, J. R.; Marston, Richard A.; Morisawa, Marie (New York : Elsevier Health Sciences, 2000)
08